Literature Study Of The Effectiveness Of Flexible Pads As Submarine Pipeline Protection Due To Anchor Falls - Juswan Sade (Collaborate Engineering Daily Book Series, 2023)
Subsea pipelines are critical transportation infrastructure for the offshore oil and gas industry. With the increasing construction of undersea pipeline networks and the construction of ports on coastlines, cases often occur where the landing sections of undersea pipelines intersect shipping lanes. Some of the problems faced in underwater pipes include damage to underwater pipes due to shifting and kinking, pipes hitting ship anchors, and pipes being dragged by ship anchors so that they are damaged and broken. Subsea pipelines located in shipping areas or near docks are vulnerable to the effects of falling anchors. Dropping an anchor on a pipe is one of the most severe accidents in the oil and gas industry. Considering that the impact of the anchor drop on the pipe directly affects the safety of the pipe vessel and the cover layer design, this test mainly measures and analyzes the force on the pipe when the anchor is dropped. The main objective of this study is to determine how dimensions and material composition have a significant influence on the protection of underwater pipelines. In this research, a series of discussions were carried out regarding physical model testing to study the dynamic response of a pipe network with various protection methods affected by falling anchors. The results of the two tests show that using flexible pads as a layer to protect underwater pipes is very effective and has minimal impact on underwater pipes if anchors or other heavy objects fall. Applying flexible stone pads can provide the best protection with the lowest strain and length that affects the pipe.